CO2 laser tonsillectomy: a comparison with conventional technique - ABM Tofazzal Hossain; Md Arif Hossain Bhuyan; Shahnaz Afroza; Shaila Kabir; AHM Zahurul Huq (Society of Otorhinolaryngologists & Head Neck Surgeons of Bangladesh, 2009)
Objective: To define the advantages and disadvantages of CO2 laser tonsillectomy compared with conventional method.